(untitled) (Journal of International Studies, 2020)
Nigeria is a sovereign country located in the area of West Africa bordering on the Gulf of Guinea. The country has a total area of 923, 769sq km (a little more than twice the size of California). Its physical size makes Nigeria the third largest country in Sub-Saharan Africa. The country’s terrain consists of the lowlands in the South with mountainous formations in the South-east, which merge into the hills and plateaus of the Central belt and the plains of the far north. The climate varies from the largely equatorial climates in the South to the tropical climates in the centre and the North (Ekoko, 1990). It is also the most populous country in Africa, with a population of about 160 million (2006 census), and a population growth rate estimate of 3%. The country is bordered on the west by the Republic of Benin and the Republic of Cameroon, on the south by the Atlantic Ocean, and on the north by Niger Republic and the Republic of Chad. Nigeria is endowed with numerous natural resources, the most important being petroleum and natural gas, found in the Niger Delta areas of the country. Coal, iron ore, tin, limestone, zinc, lead, gold, precious stones, and uranium are found across the country.There are many ethnic groups, roughly categorized into the majority ethnic groups and the minority ethnic groups. The majority groups are namely, the Hausa-Fulani of the North, the Yoruba of the South-west, and the Igbo of the South-east. The hundreds of so-called minority ethnic groups include the Igala, Tiv, Idoma, Junkun, Angas, Birom and others in the Central-belt, the Edo, Urhobo and Itshekiri in the Mid-west, the Ijaw, Efik, Ibibio and Ogoni in the South-south, and the Kanuri, Gwari and Kataf of the far-North. On the whole, it is estimated that the country has more than 250 ethnic groups (Osaghae, 1998). English is the official language in Nigeria, by virtue of the country being a former colony of Britain. Christianity, Islam and traditional beliefs are the religions in the country, and although there is no state religion, the various tiers of government in the country are often involved in aspects of some of these religions, including state sponsorships of annual Muslim and Christian pilgrimages to the Holy lands.